Advanced computational techniques for predicting 3D printing distortion in selective laser melting processes of Aluminium AlSi10Mg - Moch. Agus Choiron; Anindito Purnowidodo; Achfas Zacoeb; Gembong Edhi Setyawan; Willy Artha Wirawan; Yudhi Ariadi; Allan E.W. Rennie; Diva Kurnianingtyas (Mechanical Engineering for Society and Industry, 2025)
Distortion for 3D printing using Selective Laser Melting (SLM) on AlSi10Mg aluminium is an important issue that affects the final manufactured product. This research aims to develop a finite element method (FEM)-based computational simulation and experimental validation to predict distortion in 3D printed products using SLM. The study results found that the variation of 3D printing position affects the resulting product's distortion and mechanical properties. The 90° part print position results in smaller distortion of 0.303 and 0.335 mm than the 0° part print position of 0.329 and 0.378, respectively, making it more suitable for high-precision applications. This study confirms the importance of scan orientation in controlling distortion in the SLM process, which can be used as a guide for optimal printing parameters. With proper orientation selection, the risk of distortion or defects in SLM products can be minimised, and industrial production efficiency can be improved.